Online reviews credibility: Implications on traveller’s decision making - Lopes, Romeu (2013)
The social web is the ideal place to share information, experiences and preferences among consumers. Nowadays, online reviews and recommendations are becoming increasingly important and seen as a new digital form of word-of-mouth, a key topic for researchers. Despite the significant body of literature about electronic word-of-mouth (EWOM), there is a lack of research that analyzes the phenomenon in the context of the hospitality industry, its drivers, conditioning factors and impacts. This research aims to highlight the online reviews as a reliable and important source of information for travellers, with possible implications in their decision making process. It is expected to yield some relevant contributions to academia, marketing and management in the tourism and hotel businesses.